Manajemen Sumber Daya Manusia (SDM) dalam Meningkatkan Profesionalisme Guru Al-Qur’an di SDS Shibghah Akhlak Quran (SAKURA) Kota Bekasi - Hasanah, Auliya; Irhamsyah, Fahmi; Junah (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2025)
The high rate of Al-Qur’an illiteracy in Indonesia reflects the low quality of Qur’anic education, largely due to the lack of teacher professionalism. This study aims to describe how human resource management (HRM) is applied to enhace the professionalism of Al-Qur’an teachers at SDS Shibghah Akhlak Quran (SAKURA) in Bekasi City. A descriptive qualitative approach was employed, using observation, interviews, and documentation as data collection techniques. The findings reveal that the application of POAC management functions (planning, organizing, actuating, and controlling) has had a positive impact on improving teacher professionalism, particularly in personal, pedagogical, and spiritual aspects. However, several shortcomings were identified, including inadequate documentation system, the absence of competency-based performance evaluations, and limited teacher training and technological literacy. A SWOT analysis was used to assess the school’s internal and external conditions and to formulate more structured and sustainable HR development strategies.